Effect of anxiety on COVID‐19 infection in hemodialysis patients. Issue 4 (26th November 2021) - Ozkan Kurtgoz, Pervin; Sackan, Fatih; Kızılarslanoglu, Muhammet Cemal; Bilgin, Ozlem; Guney, Ibrahim
Abstract: Some evidence suggests that anxiety deteriorate the immune system. We aimed to determine the effect of anxiety on COVID‐19 infection in hemodialysis (HD) patients. Our study was conducted with 80 HD patients. State‐Trait Anxiety Inventory (STAI), and Beck Anxiety Inventory (BAI) questionnaires were administered between April 15 and May 1, 2020. These patients were followed up for about 8 months and COVID‐19 infection, hospitalization, and death rates were recorded. Twenty‐one (26%) of the patients were diagnosed with COVID‐19 infection. Fourteen out of twenty one (66.6%) of the patients were hospitalized, and 8/21 (38%) of them died due to COVID‐19. STAI‐S ( p = 0.006) and BAI ( p = 0.021) scores were found to be higher and STAI‐T ( p = 0.040) score was found to be lower in HD patients who were infected with COVID‐19 compared to without, at the follow‐up period. It might be concluded in this study that COVID‐19 was more common in anxious HD patients.